Teologi Tongkonan: Berteologi dalam Konteks Budaya Toraja - Ezra Tari (EPIGRAPHE: Jurnal Teologi dan Pelayanan Kristiani, 2018)
Theology in Indonesia Context, especially in Toraja culture is a necessity. This paper shows how to conduct theology in the context of Toraja culture. Where with the correct understanding of Christ and his work as true God and true human with theological and cultural positions. So that criticism is a preparation step towards theological reflection. This study provides a response from the Bible's point of view of the position of believers in the middle of culture. To obtain data in accordance with the problems that have been described previously, the authors conducted research with qualitative descriptive research. In general, the approach used is to create a difference between the Gospel and Culture. But theology and the attitude of believers develop thoughts that transform culture. The Gospel and Culture constantly dialogue in finding values that are capable of transforming humans who embrace the culture. The most important thing in establishing a culture and the gospel is to produce peace or hospitality for the people. AbstrakBerteologi Dalam Konteks di Indonesia, terutama dalam budaya Toraja adalah sebuah keniscayaan. Tulisan ini menunjukkan bagaimana berteologi dalam konteks dalam budaya Toraja. Di mana dengan pemahaman yang benar tentang Kristus dan karya-Nya sebagai Allah sejati dan manusia sejati dengan posisi teologi dan budaya. Sehingga kritik adalah langkah persiapan kearah refleksi teologis. Penelitian ini memberikan tanggapan dari sudut pandang Alkitab bagaimana posisi sebagai orang percaya yang ada ditengah kebudayaan.Untuk mendapatkan data sesuai dengan permasalahan yang telah dipaparkan sebelumnya, maka penulis melakukan penelitian dengan jenis penelitian deskritif kualitatif. Pada umumnya pendekatan yang digunakan adalah menciptakan perbedaan antara Injil dan Kebudayaan. Namun Teologi dan sikap orang percaya mengembangkan pemikiran yang mentransformasi budaya. Injil dan Kebudayaan terus-menerus berdialog dalam menemukan nilai yang mampu mengubahkan manusia yang menganut kebudayaan. Hal yang sangat penting dalam menjalin kebudayaan dan injil adalah menghasilkan kedamaian atau hospitalitas bagi umat.